An assessment of environmental conditions in bedrooms of contemporary low energy houses in Scotland. Issue 3 (May 2014) - Sharpe, T. R.; Porteous, C. D. A.; Foster, J.; Shearer, D.
This paper describes the monitored environmental conditions in the bedrooms of 26 low energy houses in Scotland, include both naturally ventilation and houses with mechanical ventilation with heat recovery systems (MVHR). The context of the paper is the performance gap that is emerging between design predictions and actual performance of housing, and this paper focuses on the environmental performance of bedrooms. Bedrooms are of particular interest as they are the spaces in which occupants have the greatest exposure to the indoor environment, and in which conditions are relatively constant. The study indicates that ventilation is generally poor in these spaces and that both temperature and humidity frequently exceed accepted parameters for comfort and health. Increased window opening is a mitigating factor, but effects are limited by overall ventilation strategies.